EVALUATION OF THE WASTE WATER TREATMENT INSTALLATION OF THE SELE BE SOLU REGIONAL PUBLIC HOSPITAL SORONG CITY - Dwangga, Mierta; Asriadi, Asriadi; Noor Irawan, Mochammad Aziz (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2024)
The Hospital Wastewater Treatment Plant (WWTP) is a system of hospital wastewater treatment designed based on the characteristics of waste water entering from several sources of waste discharge. The research location is at Sele Be Solu Regional Hospital, Sorong City, West Papua. The land owned by Sele Be Solu Regional Hospital is approximately 120,000 m2, and the number of beds is 158. This study uses laboratory tests to measure the quality of wastewater and the wastewater treatment plant. From the calculated results, the maximum discharge produced by Sele Be Solu Regional Hospital is 4343 m3/month. With the actual pollution load for the BOD parameters of 26.36 kg/month, COD of 157.98 kg/month, and TSS of 38,343 kg/month, all three are greater than the maximum pollution load allowed, namely for the BOD of 12,708 kg/month, COD of 105.9 kg/month, and TSS of 211.8 kg/month. The quality of wastewater from the Sele Be Solu Regional Hospital's wastewater treatment plant in 2017, which was tested by PT. Kehati Lab Indonesia, showed that all parameters met the quality standard requirements of the Minister of Environment Regulation Number P.68 of 2016. Meanwhile, the quality of processed wastewater in 2019 and 2021 showed that the parameters for Coli Group germs exceeded the permitted quality standards, while other parameters still meet the quality standards.